Combined source-effect of photovoltaic generator and bi-directional dc–dc battery charger on inverter control dynamics - Roosa-Maria Sallinen; Tuomas Messo (The Journal of Engineering, 2019)
This study presents a method to solve the dynamic model of a grid-connected photovoltaic (PV) inverter with battery energy storage. A three-phase grid-connected solar-battery system is studied using small-signal state-space modelling in the synchronously rotating dq-reference frame. The combined effect of a PV generator and a bi-directional dc–dc battery charger (BC) on the inverter dynamic behaviour is analysed. It is shown that the characteristic right-half-plane pole in the PV inverter's dc-link voltage control dynamics shifts to a lower frequency when the BC is connected, which improves the stability of the system and allows a lower bandwidth for the dc-link voltage control.